PENGARUH DUKUNGAN ORGANISASI TERHADAP KOMITMEN ORGANISASIONAL DAN KINERJA ANGGOTA - MujiLestari, Dian; Ratnawati, Kusuma (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The objective of this research is to identify the effect of organizational support on organizational commitment and member performance. This study is categorized as an associative research, which examines the effect of organizational support on the organizational commitment and performance of the members of student research institution of Universitas Brawijaya. The data was harvested from online questionnaires distributed to 47 respondents and was analyzed using Partial Least Squares in SmartPLS 3.0. The results indicate that organizational support positively and significantly influences organizational commitment, that organizational support positively and significantly influences member performance, and that organizational commitment does not significantly affect member performance. This research is able to prove that members of the said institution whose funding application for the 2021 PKM Dikti was approved and who received sufficient support from their organization are able to increase their organizational commitment to perform. The outcome finally leads to their higher performance in their organization.